Pengaruh Metode Storytelling dengan Media Buku Cerita Bergambar Terhadap Kemampuan Menyimak dan Berbicara Anak Usia 5-6 Tahun di TK Hang Tuah Perwakilan Bengkulu - Sari, Fesi Purnama (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to determine the significant effect between the storytelling method using storybooks on the ability of listening skills and speaking skills of children aged 5-6 years at Hang Tuah Kindergarten, Bengkulu Representative. This type of research is quantitative research using data collection techniques using observation and documentation. Sample in this study in the experimental class 22 students and control class 19 students. Based on the calculation of spss 20 by comparing the development of listening and speaking of children between experimental groups, it is known that the manova test analysis to determine the significant effect of picture storybook media on listening skills and speaking skills of group B kindergarten children. The results showed that the sig value. ≤ 0.05, then H1 is accepted, which means that the use of picture storybook media has a significant effect on children's listening and speaking skills. The results of the analysis show that the results of the manova test can be seen in the Hotelling's Trace value of 0.724. The F value is 13.756 and the sig value is 0.000 <0.05. This means that H1 is accepted because the sig value <0.05. It can be interpreted that there is a significant effect of picture storybooks on the listening and speaking skills of Hang Tuah Bengkulu kindergarten children simultaneously.